(untitled) (قضايا سياسية, 2022)
This study discusses the impacts of women’s empowerment on the realization of sustainable development goals and the improvement of institutional conduct. This topic’s significance stems from its representation of a social issue and new visions of achieving comprehensive sustainable development. The problem of this research addresses the lack of interest in women’s empowerment in certain economic sectors, which negatively affects the achievement of economic, cultural, and ecological balance, along with the decrease of functionality in those economic sectors. The study aims to define women’s empowerment in accordance with the aspects of sustainable development and the elements of functionality, and it aims to illustrate the correlation between empowerment and sustainability to achieve optimal performance. In addition, this paper seeks to demonstrate the effects of woman’s empowerment on the realization of sustainable development and improving functionality relying on the following hypothesis: empowering the woman that possesses skills, abilities, and resources leads to the effective realization of sustainable development aspects, and it ensures optimal functionality. The research reaches a set of conclusions, the most important of which was that the empowerment of women economically, socially, environmentally, and technically contributes effectively to the improvement of the process of administrative empowerment.